2021
DOI: 10.1002/jmv.27339
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of SARS‐CoV‐2 S protein is critical for S‐mediated syncytia formation and virus entry

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the ongoing coronavirus disease 2019 (COVID-19) pandemic. The S protein is the key viral protein for associating with ACE2, the receptor for SARS-CoV-2. There are many kinds of posttranslational modifications in S protein. However, the detailed mechanism of palmitoylation of SARS-CoV-2 S remains to be elucidated. In our current study, we characterized the palmitoylation of SARS-CoV-2 S. Both the C15 and cytoplasmic tail of SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…This interaction causes the formation of multinucleated syncytia which may contribute to virus propagation and to tissue damage. While syncytia were never observed with SARS-CoV-1, infection with SARS-CoV-2 is reported to induce the formation of multinucleated cells in vitro (153)(154)(155)(156) as well as in vivo (154,(157)(158)(159), leading to the fusion of pneumocytes (157) with the contribution of lymphocytes (159) in the lungs. The propensity of the SARS-CoV-2 spike to induce the formation of multinucleated cells could be related to the processing by cellular proteases, such as furin and TMPRSS2 (156,159), which activates and unleash the fusogenic potential of the viral glycoprotein not only on the viral particle but also on the cell surface.…”
Section: Syncytia Formation By Sars-cov-2 Spike: a Fusogenic Interaction Of Infected And Non-infected Cellsmentioning
confidence: 99%
“…This interaction causes the formation of multinucleated syncytia which may contribute to virus propagation and to tissue damage. While syncytia were never observed with SARS-CoV-1, infection with SARS-CoV-2 is reported to induce the formation of multinucleated cells in vitro (153)(154)(155)(156) as well as in vivo (154,(157)(158)(159), leading to the fusion of pneumocytes (157) with the contribution of lymphocytes (159) in the lungs. The propensity of the SARS-CoV-2 spike to induce the formation of multinucleated cells could be related to the processing by cellular proteases, such as furin and TMPRSS2 (156,159), which activates and unleash the fusogenic potential of the viral glycoprotein not only on the viral particle but also on the cell surface.…”
Section: Syncytia Formation By Sars-cov-2 Spike: a Fusogenic Interaction Of Infected And Non-infected Cellsmentioning
confidence: 99%
“…DHHC20, -8, and -9 were verified to play certain roles in SARS-CoV-2 spike protein(S) and enveloped protein (Abdulrahman et al, 2021;Mesquita et al, 2021;Puthenveetil et al, 2021). However, conflicting results regarding the palmitoylation sites and palmitoylation enzymes of SARS-CoV-2 spike protein were obtained by different researchers (Mesquita et al, 2021;Puthenveetil et al, 2021;Zeng et al, 2021;Li et al, 2022). Li et al found the cysteines of C-terminal and N-terminal C15 of the spike protein were palmitoylated (Li et al, 2022), while Wu et al reported that N-terminal C15 mutant did not affect the Sacylation of the spike (Wu, Zhang et al, 2021).…”
Section: Palmitoylation Of Viral Proteinsmentioning
confidence: 99%
“…However, conflicting results regarding the palmitoylation sites and palmitoylation enzymes of SARS-CoV-2 spike protein were obtained by different researchers (Mesquita et al, 2021;Puthenveetil et al, 2021;Zeng et al, 2021;Li et al, 2022). Li et al found the cysteines of C-terminal and N-terminal C15 of the spike protein were palmitoylated (Li et al, 2022), while Wu et al reported that N-terminal C15 mutant did not affect the Sacylation of the spike (Wu, Zhang et al, 2021). Using computational, lipidomic, and biochemical approaches, Mesquita et al deciphered the roles of zDHHC20 and zDHHC9 in the palmitoylation of the C terminal cysteines of spike protein in in vivo and in vitro conditions (Mesquita et al, 2021).…”
Section: Palmitoylation Of Viral Proteinsmentioning
confidence: 99%
“…This suggests that in addition to DHHC9, DHHC15 or DHHC20 can also palmitoylate the spike protein. Others have also shown that DHHC20 is capable of palmitoylating the SARS-CoV-2 spike protein(5,26,60). Among these reports, while Mesquita et al(26) and Li et al(60) also found DHHC9 as a potential spike palmitoylating PAT, Puthenveetil et al did not identify DHHC9 in their screen(5).…”
mentioning
confidence: 99%
“…Others have also shown that DHHC20 is capable of palmitoylating the SARS-CoV-2 spike protein(5,26,60). Among these reports, while Mesquita et al(26) and Li et al(60) also found DHHC9 as a potential spike palmitoylating PAT, Puthenveetil et al did not identify DHHC9 in their screen(5). In this context, it is reasonable to assume that spike protein palmitoylation may be carried out by different DHHC proteins in different cellular compartments during the viral life cycle.…”
mentioning
confidence: 99%